Analisis Pengajuan Publikasi AIP Di PIA Wilayah Denpasar - Rashifaldo, Naufal; Amir, Elfi; Maruli Sinaga, Togi Adnan (Politeknik Penerbangan Indonesia Curug, 2025)
This research was conducted at the Denpasar Region Aeronautical Information Service Unit during the On the Job Training (OJT) program with the aim of analyzing the process of submitting changes to Aeronautical Information Publication (AIP) data and the obstacles faced. the research method used is descriptive qualitative and observation. The results of the study revealed obstacles related to the completeness and format of the data submitted by the data source, as happened in the case at UPBU Airport under the Denpasar area. These obstacles cause obstruction in the publication process. To overcome this problem, the author recommends the implementation of socialization of AIP submission procedures, LOCA document updates, and additional AIS personnel to improve the efficiency of the publication process.